Training RA Al Mahabbah Children's Foreign Language Skills through English Songs - Afdhalina; Novi Chinthia Yusnita; Kharida Shaleha (Outline Publisher, 2024)
English already plays an important role in the teaching and learning process for early childhood. However, you must pay attention to the right method when teaching a foreign language to children. Songs are a method of learning English for young children, making learning more fun. The aim of this service is to train the abilities of young children at RA Al Mahabbah in learning foreign languages ​​through the song presentation method. This service is carried out by preparing several steps such as: preparing 2 English songs, listening to them, singing them and repeating them together. The results obtained from this service are that the children are very enthusiastic about following and singing songs together and they feel very happy by moving and singing alternately with one another.